Statistics tutor : - Allen, Joseph D. (John Wiley & Sons, 2000)
This comprehensive software tutorial program and exercise manual makes use of the computer to tackle and present to readers conceptually-difficult statistical concepts. Users are introduced to a variety of difficult concepts in a truly dynamic way.